Effects of maternal and fetal choline concentrations on the fetal growth and placental DNA methylation of 12 target genes related to fetal growth, adipogenesis, and energy metabolism. Issue 2 (9th December 2020) - Nakanishi, Misao; Funahashi, Nobuaki; Fukuoka, Hideoki; Nammo, Takao; Sato, Yuichi; Yoshihara, Hajime; Oishi, Hajime; Tanaka, Mamoru; Yano, Tetsu; Minoura, Shigeki; Kato, Norihiro; Yasuda, Kazuki
Abstract: Aim: We performed a birth cohort study involving 124 mother–infant pairs to investigate whether placental DNA methylation is associated with maternal choline status and fetal development. Methods: Plasma choline concentration was assayed longitudinally in the 1st and 3rd trimesters and at term‐pregnancy in mothers and cord blood. Placental DNA methylation was measured for 12 target candidate genes that are related to fetal growth, adipogenesis, lipid and energy metabolism, or long interspersed nuclear elements. Results: Higher maternal plasma and cord blood choline levels at term tended to associate with lower birthweight ( r = −0.246, P  < 0.013; r = −0.290, P  < 0.002) and body mass index (BMI) at birth ( r = 0.344, P  < 1E−3; r = −0.360, P  < 1E−3). The correlation between maternal plasma choline level and cord blood choline level was relatively modest ( r = 0.049, P = 0.639). There was an inverse correlation between placental DNA methylation at the retinoid X receptor alpha ( RXRA ) gene and maternal plasma choline level ( r = −0.188 to r = −0.452, P = 0.043 to P  < 1E−3 at three points). RXRA methylation level was positively associated with birthweight and BMI at birth ( r = 0.306, P = 0.001; r = 0.390, P  < 1E−3). Further, RXRA methylation was inversely correlated with RXRA gene expression level ( r = 0.333, P  < 1E−3). Conclusion: Our results suggest that the association between maternal choline status and placental RXRA methylation represents a potential fetal programing mechanism contributing to fetal growth.